Efficient Multi-Composite Cement Made of Granulated Blast Furnace Slag (GBFS) and Flash-calcined Sediment - Mahfoud Benzerzour; Duc Chinh Chu; Mouhamadou Amar; Joelle Kleib; Nor-Edine Abriak; Jaouad Nadah (Salehan Institute of Higher Education, 2023)
The objectives of this study were to find out in detail how well granulated blast furnace slag (GBFS) could be replaced by flash-calcined sediment (SF sediment) in terms of hydration kinetics and mechanical-microstructural properties when developing an eco-friendly cement binder. The results indicated that the SF sediment substitution with a rate of 25% wt significantly improved the hydration kinetics of cement compared to the reference. This contributed to a considerable enhancement of the mechanical-microstructural properties of the mortar containing the SF sediment. By comparison with the reference, the strength of multi-composite cement-based mortar increased by 33% at 2 days and by 4.5% at 28 days, whereas its porosity decreased by 16.32% and by 12.44% for the same period. The SEM-EDS result showed that the SF sediment substitution did not significantly modify the chemical composition of the C-S-H phase, with a Ca/Si ratio range of 1.82 to 2.84 for both cement pastes. Moreover, Mg2+ and Al3+ions were two principal elements incorporated in C-S-H gels, with different ratios depending on the Ca/Si ratio of C-S-H gels. A novel model established from a combination of the curve fitting method and Power’s approach allowed for accurate prediction of the strength development of multi-composite cement-based mortars. Overall, the SF sediment substitution could be considered a promising option to develop a more eco-friendly cement binder, while the novel approach could be used as a reliable model for the strength prediction of blended cement. Doi: 10.28991/CEJ-2023-09-11-02 Full Text: PDF